Tradisi Robo’–robo’ Suku Melayu di Kecamatan Sandai, Kabupaten Ketapang, Kalimantan Barat (Studi Living Hadis) - Faiza Hanan, Fatkhiyah dan Nafisah Alhayataini (al Dhikra | Jurnal Studi Qur'an dan Hadis, 2022)
This study aims to discuss the phenomenon of living hadith in the Robo'-robo' tradition carried out by the people of Sandai, Ketapang district, West Kalimantan. Regarding Robo'-robo', this is a tradition that is carried out on the last Wednesday of the month of Safar where according to the people around this tradition it is a form of ritual of rejecting reinforcements to obtain safety and blessings. The focus on the discussion of this research is related to how the Prophet's traditions live in the traditions of the community. The author uses qualitative research methods, by interacting or interviewing and observing. While the theory used in this study is the sociology of knowledge of Karl Mannheim which is focused on three variables, namely first, objective, expressive and documentary meanings. This research found that the objective meaning of the Robo-robo tradition of the Sandai people is as a tradition of a teaching instilled from the ancestors of the Malay clergy, which then maintains its existence until today, unchanged. While the expressive meaning is the behavior of traditional rituals, there are prayers that are said, including the prayer sayyidina Ukasyah or Akasah, the prayer for safety and the prayer for refusing to take custody which is said in the hope that Allah SWT will grant all his wishes. Then the meaning of the documentary is that this tradition is the identity of the Sandai people.